Pengaruh Warna Ruang Henti Kendaraan terhadap Persepsi dan Perilaku Pengendara Kendaraan di Cilacap - Basuki, Ahmad; Hadi, Suprapto; Shofiah, Siti; Zuhrianto, Farhan Afif; Bunga Riska Ayu, Brasie Pradana Sela (Syntax Corporation, 2023)
The abstract should briefly describe the content and scope of your paper and identify the objective(s), its methods and its results, conclusions, and implication of study. It should be about 150 words (maximum), followed by three to five keywords related to your article. [TNR 9pt] Keywords: keyword1; keyword2; keyword3; keyword4; keyword5